PENGARUH CORPORATE SOCIAL RESPONSIBILITY TERHADAP PREFERENSI MEREK PERUSAHAAN PADA PT. BANK PEMBANGUNAN DAERAH BALI - Fajariani, A.A.; Sulistyawati, Eka (E-Jurnal Manajemen, 2015)
This study aimed to determine the effect of corporate social responsibility for the company's brand preference. The location of this research in Denpasar. The sample used 65 respondents, using the technique of sampling proposive. The analysis technique used is multiple linear regression analysis with the classical assumption and hypothesis testing. Based on the results of multiple linear regression is known to have a positive influence of CSR in the context of economic performance, environmental performance and social performance significant positive effect on brand preference. This means that if each of these performance increases, brand preference will also increase.
Keywords: Corporate Social Responsibility, Brand Preferences